Kualitas Pelayanan Butler Pada Masa Pandemi Di The Ritz - Carlton Bali - I Gede Darmawijaya; Gede Edwin Permana; Ida Ayu Sri Puspa Adi (Program Studi Manajemen Divisi Kamar, 2022)
This study aims to reveal the quality of Butler service during the pandemic of Covid-19 at The Ritz-Carlton Bali. Data were collected through interview, documents, and observation techniques. The informant was Chief Butler who knew the day to day of Butler services. Qualitative data analysis was used in this research by referring to Parasuraman’s theory on service quality gap. The results of the analysis indicated that the quality of Butler's service during the pandemic at The Ritz-Carlton Bali was very good with the conformance rate of 97%. This finding showed that the butler services conformed to service standard and were able to follow all measures of CHSE.